2016
DOI: 10.1016/j.ijpe.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of internal communication and employee satisfaction on supply chain integration

Abstract: Lastly, it may be as important to carefully craft communication campaigns aimed at employees as those aimed at customers since the former appear to lead to more effective integration with customers, which elsewhere has been linked to improved financial and market performance.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(157 citation statements)
references
References 111 publications
(194 reference statements)
3
144
0
10
Order By: Relevance
“…Supply chain integration in companies is indicated by the ease of accessing other unit data and the integration of reports on the work of company units, and enabling to provide satisfaction to company employees because it is able to provide satisfaction to employees as key persons to the supervision given at work and work colleagues. This research is in line with the research of Jacobs et. al., (2016) which states that the impact of supply chain integration has an impact on employee satisfaction with internal communication in manufacturing companies in China, because it can access the warehouse inventory on a voluntary basis.…”
Section: Analysis and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Supply chain integration in companies is indicated by the ease of accessing other unit data and the integration of reports on the work of company units, and enabling to provide satisfaction to company employees because it is able to provide satisfaction to employees as key persons to the supervision given at work and work colleagues. This research is in line with the research of Jacobs et. al., (2016) which states that the impact of supply chain integration has an impact on employee satisfaction with internal communication in manufacturing companies in China, because it can access the warehouse inventory on a voluntary basis.…”
Section: Analysis and Discussionsupporting
confidence: 93%
“…Second hypothesis (H2) is the implementation of TQM in a company influences Supply Chain Integration. Jacobs et al (2016) also learns that supply chain integration influences the employee satisfaction with internal communication in a manufacturing company in China. The company facilitates the warehouse inventory in real-time.…”
Section: Research Framework Conceptmentioning
confidence: 99%
“…We found a significant relationship between a high JS and a high OIE outside the hospital. Jacobs, Yu, and Chavez () indicated that “internal communication” has a significant positive effect on JS. Internal communication refers to communication that creates an atmosphere of respect for all employees within the organisation.…”
Section: Discussionmentioning
confidence: 99%
“…Semakin tinggi kemampuan seorang karyawan dalam berkomunikasi, maka akan semakin tinggi pula nilai kinerja karyawan tersebut [5]. Penggunaan kriteria dalam penelitian ini diambil dari beberapa penelitian terdahulu yang kemudian dilakukan dilakukan analisis dan penentuan termasuk kedalam kriteria positif atau termasuk dalam kriteria negatif [12].…”
Section: Daftar Kriteria Yang Dapat Digunakan Untuk Penilaian Kinerjaunclassified